PERAN PENGALAMAN PELANGGAN DALAM MEMEDIASI PENGARUH KUALITAS LAYANAN, CITRA MEREK TERHADAP LOYALITAS PELANGGAN - Resa Budianti Utami; Sri Padmantyo (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this study is to analyze the role of customer experience in mediating the influence of service quality, brand image on customer loyalty. This research method uses quantitative. The population in the study was customers of jenang teguh Raharjo and people who had bought jenang Teguh Raharjo products. While the sample in this study amounted to 200 respondents. Data retrieval technique using google form questionnaire data. The sampling technique used by researchers is purposive sampling technique.  The data analysis technique in this study uses Partial Least Square (PLS) using the help of SMARTPLS Software. The result of this study is that service quality has a significant positive effect on customer experience. Brand Image has a significant positive effect on customer experience. Service Quality has a significant effect on Customer Loyalty. Brand Image has a significant positive effect on customer loyalty. Customer experience has a significant positive effect on customer loyalty. Customer experience has a positive and significant effect on service quality mediated by customer loyalty. Customer experience has a positive and significant effect on brand image mediated by customer loyalty